Factors affecting the decision to pay for an improved solid waste collection service among households in subdivision in Iloilo City. - Navallasca, Julius Lawrence B.
Iloilo City, a highly-urbanized city, is not exempted from the problem of solid waste collection plaguing the urban areas. This study described the willingness-to-pay decision among 100 households in subdivisions in Iloilo City for an improved solid waste collection service. A survey using interview schedule was conducted in five residential subdivisions in the five districts of Iloilo City. Both descriptive and explanatory statistics were used by the study. It was found that the majority of the households perceived solid waste collection as a problem in Iloilo City. Households generate an average volume of 1.40 kilograms daily relied heavily on waste collection service. Moreover 64 percent of the household are willing to pay for an improved solid waste collection service with varying desired attributes of an improved service. Age, civil status, employment, household income and number of working households were the significant factors affecting the households' decision to pay for an improved waste collection service. The study recommended that the city government should concentrate on the education and law enforcement aspects in improving the solid waste collection in the city. A more systematic waste collection service is also recommended. Finally, further studies related to improving the waste collection service are encouraged.